MULTICULTURAL EDUCATION TO BUILD THE MODERATE-RELIGIOUS CHARACTER AT BAITUL ARQAM ISLAMIC BOARDING SCHOOL - Hatta Hatta; Mursalim Mursalim; Muhammad Junaidi; Najibul Khoir; Abu Bakar Sirajo Magaji; Martha Adriana Maza (LP2M UIN KH.Achmad Siddiq Jember, 2022)
The widespread act of radicalism under the guise of Islam has placed Muslims as the accused. The discussion of jihad in Islamic teachings is often referred to as the primary source of violence. Likewise, pesantren (Islamic boarding school) is also accused of instilling radicalism. Therefore, it is urgently needed to provide an understanding of education in pesantren. Whether pesantren contribute to radicalism, or conversely, it has become a torch for moderation and respect for human rights. This research is carried out to describe the value of multicultural education and how it is taught in building the moderate-religious character at Baitul Arqom Islamic Boarding School Jember. A qualitative method with observation, interview, and documentation techniques of data collection is used for this research. The data analysis is a descriptive qualitative method, while the source and technique triangulation are shown for the validity of the data. The study highlights that in building the moderate-religious character at Baitul Arqom Islamic boarding school, kyai and teachers preach the values of honesty, tolerance, democracy, togetherness, and cooperation. These values are promoted through the comparative study of madhab books and religions, moral habituation, history, and culture. Eventually, it affects the growth of the moderate-religious character, tolerance, and mutual respect.